2010
DOI: 10.1111/j.1398-9995.2010.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Type III hereditary angio‐oedema: clinical and biological features in a French cohort

Abstract: Diagnosis of type III HAE should be based on clinical (typical attacks, often hormonally influenced), laboratory (normal C1Inh antigenic protein) and genetic (F12 gene mutation) evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 31 publications
6
57
0
2
Order By: Relevance
“…Subsequently, several family studies reported the presence of this symptomatic mutation [4,[6][7][8][9], corresponding to approximately 150 reported cases of HAE with FXII mutations (FXII-HAE). Depending on the series, the prevalence of the FXII mutation within HAE families without C1-INH deficiency would be in the order of 20-24Á5% [10,11]. Other FXII mutations have been described recently in Turkish (deletion c.971_1018 1 24del72) and Caucasian (c.892_909dup) families [12].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several family studies reported the presence of this symptomatic mutation [4,[6][7][8][9], corresponding to approximately 150 reported cases of HAE with FXII mutations (FXII-HAE). Depending on the series, the prevalence of the FXII mutation within HAE families without C1-INH deficiency would be in the order of 20-24Á5% [10,11]. Other FXII mutations have been described recently in Turkish (deletion c.971_1018 1 24del72) and Caucasian (c.892_909dup) families [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, Vitrat-Hincky et al [109] Duan et al [110] not only confirmed the F12 gene mutation (gene-codifying coagulation factor XII) in women of the same family but also provide certain polymorphisms in the genes encoding aminopeptidase P (APP) and angiotensin-converting enzyme (ACE). It highlights the role of the BK-catabolizing enzymes in the pathogenesis of angioedema.…”
Section: Börk Et Al Proposed To Use Fxii-hae To Name Those Cases Of mentioning
confidence: 87%
“…p.Thr328Lys has been described in patients/families from various ethnic backgrounds. These ethnicities include Arabian; 3,4 Australian; 5 Brazilian, 6 British; 7 French; 1, 8,9 German; 1,2,10 Italian; 11-13,, Jewish; 3 and Spanish. 14-16,, Haplotype studies of German, French, British, Italian, and Brazilian families have suggested a common founder.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…22 and off label use has been reported. 9,25 No data are available concerning differences in clinical management, treatment response, or prognosis between patients with variants in F12 (FXII-HAE) and variant-negative patients (U-HAE).…”
Section: How Is the Cost Effectiveness Of Alternative Diagnostic Methmentioning
confidence: 99%